Leisure and recreation as determining factors of wellbeing: The case of the Municipality of Pesqueria, Nueva León. (National Administration Journal, 2019)
This article analyze the perceptions of the inhabitants of Pesquería, Nuevo León city in Mexico about leisure and spreading as factors of social and personal well- being. Pesquería, Nuevo León has been undergoing gradual changes in its population growth, which has been quickly multiplied in the last years thanks to the arrival of big investors. This  brings  newneeds that are perceived by the community as analternative or solution to the challenges and changes in the practices of the inhabitants of Pesquería, Nuevo León. Leisure, spreading activities, also the availability of new, and more public and private recreational areas are considered as the alternative to the new prospect of municipal dynamist or urban stress. Thus, it is of social, economic, environmental and politica importance to attend this new socio- urban phenomenon that impacts this municipality inhabitant’s well-being. Therefore, the inhabitant´s perceptions will be important to define the well- being satisfiers that derivate from social programs and initiatives public or private, in order to satisfy these new social needs.
Keywords: Well-Being; Perception; Leisure, Spreading; Sustainability